Scaling junior sport competition: A body-scaling approach? - Broadbent, N.; Buszard, T.; Farrow, D.; Reid, M. (Journal of Sports Sciences, 2021)
The design of the junior sport competition environment plays a critical role in attracting and retaining children as life-long participants. Critically, however, the guidelines governing the design of junior sport are rarely scrutinized. With this in mind, our aim is to offer sports authorities a method to systematically assess the suitability of guidelines. The most popular junior ball sport competitions in Australia were assessed in relation to the scaling of task constraints and compared to children`s corresponding physical maturation and/or performance measures. This assessment enabled the calculation of pi ratios, which were then used to categorise constraints as either (1) undersized, (2) appropriately sized or (3) oversized. Results revealed that most sports` ask children to play in oversized conditions, particularly in the under 9 to under 12 age groups and in boys` competitions. The task constraints that had the highest percentage of pi ratios appropriately sized were match duration and goal size. Comparatively, ball size and field length had the highest percentage of pi ratios classified as oversized. We contend that the systematic approach applied in this article should be used by sports authorities to understand the extent of scaling constraints in junior sport.